(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Heart rate variability (HRV) and heart rate turbulence (HRT) illustrate regulation of the heart by autonomic nervous system (ANS). The autonomic nervous system plays an important role not only in physiological situations, but also in various pathological settings such as diabetic neuropathy Diabetic autonomic neuropathy is a serious and common complication of diabetes. Objective:To determine the association between HRT, HRV and diabetes control monitored by concentrations of HbA1c. Methods: In 52 patients with diabetes mellitus type II of either sex attending Cardiac Care Unit (CCU) in Al-Kadhimya Hospital, 24-hour Holter ECG monitoring was performed to evaluate time domain HRV parameters (SDNN, SDNNI, SDANN, rMSSD, pNN50) and HRT parameters (TO and TS). HBA1c was measured in all patients. Regression analysis was performed to evaluate the association between tested parameters. Results:Significant correlation has been observed between TO and SDNN, SDNNI and SDANN. TS correlated significantly with SDNN, SDNNI, SDANN, rMSSD, pNN50. We noted no correlation between HbA1c and HRV or HRT parameters. Conclusion:We concluded that HRV time domain parameters correlate with HRT in patients with diabetes mellitus. Diabetes control estimated on basis of HbA1c value did not show correlation with HRV and HRT. Key words:Heart rate turbulence HRT, Heart rate variability HRV, Diabetic Autonomic Neuropathy. HbA1c.